Electrical characterization with atomic force microscopy and low temperature transport properties of boric acid doped polyaniline with Fe3O4 nanoparticles composites - Ballestar, A.; Yakuphanoğlu, Fahrettin; Senkal, B. Filiz; Munoz, M.; Farooq, W. A. (Natl Inst Optoelectronics, 2011)
The electrical charge transport properties of the boric acid doped polyaniline with Fe3O4 nanoparticles composites have been investigated in the temperature range of 35 K to 300 K. The microstructure and electrical conductivity properties of the polymer nanocomposites were further analyzed by scanning electron microcopy (SEM) and atomic force microscopy (AFM). The electrical conductivity of the composites changes with Fe3O4 dopant. This suggests that interactions between the polymer matrix and Fe3O4 nanoparticles take place. The characteristic Mott temperature confirms the highest conductivity for the composite with 5%wt dopant. The charge transport mechanism of the composites varies from three dimensional hopping to tunneling mechanism. It is demonstrated that the boric acid doped polyaniline with Fe3O4 nanoparticles composites are typical organic semiconductors.
Keywords: Fe3O4; Electrical properties; Organic semiconductor; Nanocomposites